2018
DOI: 10.1074/jbc.m117.809913
|View full text |Cite
|
Sign up to set email alerts
|

PH domain leucine-rich repeat protein phosphatase 2 (PHLPP2) regulates G-protein–coupled receptor kinase 5 (GRK5)-induced cardiac hypertrophy in vitro

Abstract: PH domain leucine-rich repeat protein phosphatase (PHLPP) is a serine/threonine phosphatase that has been shown to regulate cell growth and survival through dephosphorylation of several members of the AGC family of kinases. G-protein-coupled receptor kinase 5 (GRK5) is an AGC kinase that regulates phenylephrine (PE)-induced cardiac hypertrophy through its noncanonical function of directly targeting proteins to the nucleus to regulate transcription. Here we investigated the possibility that the PHLPP2 isoform c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Recently, GRK5 activity has been found regulated by PH domain leucine-rich repeat protein phosphatase (PHLPP), a Ser/Thr phosphatase involved in the dephosphorylation of several kinases. Interestingly, PHLPP was able to interact with GRK5 to modulate phenylephrine-induced nuclear accumulation of GRK5 and cardiac hypertrophy in neonatal rat ventricular myocytes (NRVMs) [ 59 ].…”
Section: Cardiac Roles Of Grk5mentioning
confidence: 99%
“…Recently, GRK5 activity has been found regulated by PH domain leucine-rich repeat protein phosphatase (PHLPP), a Ser/Thr phosphatase involved in the dephosphorylation of several kinases. Interestingly, PHLPP was able to interact with GRK5 to modulate phenylephrine-induced nuclear accumulation of GRK5 and cardiac hypertrophy in neonatal rat ventricular myocytes (NRVMs) [ 59 ].…”
Section: Cardiac Roles Of Grk5mentioning
confidence: 99%
“…PHLPP2, a pleckstrin homology domain leucine‐rich repeat protein phosphatases (PHLPP) isozyme, catalyzes the dephosphorylation of AGC kinases including Akt . Maintaining balanced levels of PHLPP2 expression is essential in preventing pathologies, as changes in steady‐state levels of PHLPP2 are correlated with many diseases including diabetes, hepatic steatosis and cancer . Recently, many studies have shown that PHLPP2 expression is ubiquitously lost in multiple cancers and plays a key role in a wide range of biological processes such as cancer cell proliferation, metastasis, autophagy and apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…4 Maintaining balanced levels of PHLPP2 expression is essential in preventing pathologies, as changes in steadystate levels of PHLPP2 are correlated with many diseases including diabetes, hepatic steatosis and cancer. 5,6 Recently, many studies have shown that PHLPP2 expression is ubiquitously lost in multiple cancers and plays a key role in a wide range of biological processes such as cancer cell proliferation, metastasis, autophagy and apoptosis. [6][7][8][9][10][11][12] PHLPP2 regulates several cellular pathways in cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is indispensable to keep PHLPP2 expression in balance for pathological prevention as the change of PHLPP2 steady-state level is connected with various diseases, including diabetes, hepatic steatosis and cancers. 16,17 Recently, many studies have unveiled that PHLPP2 is ubiquitously lost in various cancers and plays an important role in multiple biological processes, such as cancer cell proliferation, metastasis, autophagy and apoptosis. [18][19][20][21][22][23] Nonetheless, the diagnostic and prognostic significance of PHLPP2 in CC have not been fully researched.…”
Section: Introductionmentioning
confidence: 99%